The concept of historicisms according to Abdul Majeed Al-Sharafi - YAHYA, HUDA ABDELAZIZ; SALIH, HUSSIEN HADI (Al-Adab Journal, 2023)
The concept of historicism is one of the newly developed concepts, which appeared at the end of the nineteenth century with new modernist concepts such as structuralism... etc. What we mean by historical here is the study of religious texts according to a historical vision through cognitive digging in the history of these texts in order to reach a certain truth, real and not suspicious of her. Historicity is one of the most important concepts that Al-Sharafi adopted to reach the truth of religious texts. Al-Sharafi worked to return facts and events to the reality in which they appeared and then look at them according to a new intellectual vision.